University autonomy in Vietnam : fragments beneath the consensus - Ninh, Tram (2019)
Being inspired by the trend of education reform around the world, the attempt to expand school autonomy has been one of the most remarkable orientations for higher education reform in Vietnam in recent years. There seems to be a consensus, at first glance, among the locals toward the necessity of the university autonomy and a common expectation that the university autonomy reform will be the most holistic reform to create necessary transitions to improve the whole (higher) education system. However, university autonomy in Vietnam is still a new foreign concept so that there has not been a fixed common understanding for it among the locals in Vietnam. Beneath the facial agreements on the normative principles of university autonomy, local perceptions keep being constructed and reconstructed during the implementation process, and their expectations were also differently prioritized accordingly. This is data-driven interpretive research to show how different actors in Vietnam are co-constructing their understanding and expectations toward university autonomy to fit with the specific context of the country on the base of the imported idea of school autonomy. By looking beneath the on-the-surface consensus, the research reveals variances in perceptions and different priorities for what the actors support the university autonomy reform. The initial findings show that there are indeed fragmented expectations and heterogeneity in the discussion of university autonomy. Despite the general support and common expectations toward the university autonomy, what happening is far from a holistic reform that fit all purposes – as many locals expected. In the current situation in Vietnam, there is a possibility that the discourse of university autonomy will be diverted to adapt mainly to economics expectations. Dramatic changes in political issues are hindered for facing tensions, struggles, and oppression. Meanwhile, the partial participatory approach is preventing an inclusive co-constructive understanding of university autonomy and leading to the overlooking of some social matters.